Modified zeolite as purification material in wastewater treatment: a review / Mohd Khairul Nizam Mohd Zuhan, Syaza Azhari and Muhammad Azan Tamar Jaya - Mohd Zuhan, Mohd Khairul Nizam; Azhari, Syaza; Tamar Jaya, Muhammad Azan (Universiti Teknologi MARA, 2021)
Natural zeolite is a hydrated aluminosilicate substance that has excellent ion exchange and adsorption properties and is environmentally and economically friendly. This review describes the current application and modification of zeolite in wastewater treatment using acid and surfactants, zeolite composites (such as zeolite membranes), permeable reactive barriers and photocatalysts. The properties of zeolite as well as the regeneration and desorption of cast-off zeolite are briefly reviewed. Modifications are made to improve the capability of zeolite in wastewater treatment facilities. Furthermore, this review proposes the integration of zeolite and other available technologies to treat emerging pollutants in wastewater. Different types of zeolite (natural and synthetic zeolite of different origins) are compared, and their properties are evaluated. Different type of pollutants and treatment methods involving zeolite are also discussed. Zeolite is enhanced to solve the problem of various pollutants in wastewater.